The role of moderation activities the influence of the audit committee and the board of directors on the planning of the sustainability report - Ignatia Martha Hendrati; Begench Soyunov; Riski Dwi Prameswari; Suyanto; Rusdiyanto; Dian Anita Nuswantara (Cogent Business & Management, 2023)
In order to show the consistency of agency theory as a theory to explain the influence of the Audit Committee and the Board of Directors on Sustainability, this study will explore the role of moderating actions of the Audit Committee and the Board of Directors on Sustainability. The firms that make up the demographic and research sample for this study, which uses a quantitative technique, are those that are included in the Jakarta Islamic Index for the years 2017 through 2021. The study's yearly financial report panel data. The data analysis methods employed in this study were robust, fixed effects, random effects, and ordinary least square regression. These methods are one of the regression solution approaches that may be used with a lot of flexibility in research that combines thoughts, ideas, and facts. The first study found that the audit committee had an effect on sustainability, whereas the second found that the board of directors has no effect. Due to the third and fourth conclusions of the role of activities, the audit committee and board of directors are less strong on sustainability.
Keywords: G02; G32; G34; M1; Z1; 650; activity; audit committee; board of directors; stata; sustainability